Gestational Exposure to Cigarette Smoke Suppresses the Gasotransmitter H2S Biogenesis and the Effects Are Transmitted Transgenerationally - Singh, Shashi P.; Devadoss, Dinesh; Manevski, Marko; Sheybani, Aryaz; Ivanciuc, Teodora; Exil, Vernat; Agarwal, Hemant; Raizada, Veena; Garofalo, Roberto P.; Chand, Hitendra S.; Sopori, Mohan L. (Frontiers in Immunology, 2020)
Rationale: Gestational cigarette smoke (CS) impairs lung angiogenesis and alveolarization, promoting transgenerational development of asthma and bronchopulmonary dysplasia (BPD). Hydrogen sulfide (H2S), a proangiogenic, pro-alveolarization, and anti-asthmatic gasotransmitter is synthesized by cystathionine--lyase (CSE), cystathionine-β-synthase (CBS), and 3-mercaptopyruvate sulfur transferase (3MST). Objective: Determine if gestational CS exposure affected the expression of H2S synthesizing enzymes in the mouse lung and human placenta. Methods: Mice were exposed throughout gestational period to secondhand CS (SS) at approximating the dose of CS received by a pregnant woman sitting in a smoking bar for 3 hours/day during pregnancy. Lungs from 7-day old control and SS-exposed pups and human placenta from mothers who were either nonsmokers or smokers during pregnancy were analyzed for expression of the enzymes. Measurements: Mouse lungs and human placentas were examined for the expression of CSE, CBS, and 3MST by immunohistochemical staining, qRT-PCR and/or Western blot (WB) analyses. Results: Compared to controls, mouse lungsexposed gestationally to SS had significantly lower levels of CSE, CBS, and 3MST. Moreover, the SS-induced suppression of CSE and CBS in F1 lungs was transmitted to the F2 generation without significant change in the magnitude of the suppression. These changes were associated with impaired epithelial-mesenchymal transition (EMT) – a process required for normal lung angiogenesis and alveolarization. Additionally, the placentas from mothers who smoked during pregnancy, expressed significantly lower levels of CSE, CBS, and 3MST, and the effects were partially moderated by quitting smoking during the first trimester. Conclusions: Lung H2S synthesizing enzymes are downregulated by gestational CS and the effects are transmitted to F2 progeny. Smoking during pregnancy decreases H2S synthesizing enzymes is human placentas, which may correlate with the risk of asthma/BPD in children.